ISTIGFAR THERAPY AS SELF-CONTROL - Adelia Fara; Indri Seta Septadina (International Islamic Medicine Forum, 2023)
Self-control is one of the personal competencies that every individual needs to have. Good behavior, constructive, and harmony with others are influenced by the individual's ability to control himself. Self-control that is well-developed in individuals will help individuals resist behavior contrary to social norms. Self-control is an individual's ability to inhibit or prevent an impulse from appearing in the form of behavior that violates or is contrary to moral standards. Self-control as organizing, guiding, regulating, and directing forms of behavior that can lead individuals to positive consequences. According to the researcher, istighfar is suitable for the client because of the meaning of asking for forgiveness from all mistakes. The problem experienced by the client is one of the mistakes, namely (cursing at his friends). This Istighfar also mentions that God is the best of human guardians. Someone asks forgiveness from Allah and asks for protection and care to protect him from bad and despicable traits. Istighfar is very important for humans. Not only because humans have a more excellent opportunity to sin, but also because Allah SWT repeatedly commands both through His words in the Qur'an and the mouth of His messenger (Rasulullah SAW).